Gothic War on Terror Killing, Haunting, and PTSD in American Film, Fiction, Comics, and Video Games - Olson, Danel (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
After 9/11, the world felt the "shock and awe" of the War on Terror. But that war also exploded inside novels, films, comics, and gaming. Danel Olson investigates why the paranormal, ghostly, and conspiratorial entered such media between 2002-2022, and how this Gothic presence connects to the most recent theories on PTSD. Set in New York/Gotham, Afghanistan, Iraq, and CIA black sites, the traumatic and weird works interrogated here ask how killing affects the killers. The protagonists probed are artillery, infantry, and armored-cavalry soldiers; military intelligence; the Air Force; counter-terrorism officers of the NYPD, NCIS, FBI, and CIA; and even the ultimate crime-fighting vigilante, Batman.
Chapter 1 Jess Walter's The Zero -- Chapter 2 J. Robert Lennon's Castle -- Chapter 3 Joyce Carol Oates' Carthage -- Chapter 4 Graphic Novels -- Chapter 5 Christopher Nolan's The Dark Knight Trilogy.
Keywords: Fiction; Goth culture (Subculture).; America-Literatures.; Motion pictures; Space; Culture; World history; Fiction Literature; Gothic Studies; North American Literature; Film Studies; Space and Place in Culture; World History, Global and Transnational History